Trilingual Supplementary Learning Material: Needs of English Learning Materials for First Grade Elementary School Students - Dewantara, Kadek Andre Karisma; Adnyani, Ni Luh Putu Sri; Suarcaya, Putu (Universitas Pendidikan Ganesha, 2024)
One of the factors that greatly influence the ineffectiveness of language learning in schools is the limited resources, including textbooks, teaching materials, and other supporting tools needed for effective English learning. Therefore, supplementary learning materials are needed that can complement the lack of teaching materials in English Classes. As an initial stage in designing and developing supplementary learning materials, this research aims to conduct a needs analysis in two elementary schools to obtain an initial picture of the needs of teachers and students as a basis for designing supplementary learning materials. This research is a qualitative descriptive study. Data were collected by interviews and direct observation. Data from the interview were analyzed descriptively. Based on the results of the analysis, it is known that there are several problems, such as teachers’ difficulties in speaking English, students’ disinterest in learning English due to limited vocabulary, and lack of interactive learning activities. Therefore, additional trilingual learning materials are needed with three equivalent languages: English, Indonesian, and Balinese. Providing learning materials covering three languages and integrated with interactive activities and games is expected to be a more inclusive and effective solution for improving students’ language skills.